Identification of VIPR2 rare and common variants in the Chinese Han population with schizophrenia - Yin, Jiajun; Zhou, Juan; Fang, Fang; Yu, Shui; Wang, Jun; Yuan, Jianmin; Zhou, Zhenhe (Frontiers in Molecular Neuroscience, 2023)
Schizophrenia is a severe and chronic psychiatric disorder with hereditary risk up to 80% as previous studies indicated. Several researches have demonstrated a significant association between schizophrenia and microduplications that overlap the vasoactive intestinal peptide receptor 2 gene (VIPR2). To further investigate potential causal VIPR2 gene variants, all exons and un-translated portions of the VIPR2 gene were sequenced using amplicon targeted resequencing in 1804 Chinese Han patients with schizophrenia and 996 healthy counterparts in the present study. Nineteen rare nonsynonymous mutations and 1 frameshift deletion was identified for schizophrenia, among which 5 variants have never been reported so far. Frequencies of rare nonsynonymous mutations were significantly different between the two groups. Specifically, the nonsynonymous mutation rs78564798 (Pallele = 0.006) as well as two rare variations in the VIPR2 gene's introns (rs372544903, Pallele = 0.026 and a novel mutation, chr7:159034078, GRCh38, Pallele = 0.048) were significantly associated with schizophrenia. Our findings add new evidence that the functional and probable causative variants of VIPR2 gene may play an important role in susceptibility to schizophrenia. Further studies on validations of VIPR2's function in the etiology of schizophrenia are warranted.